Enhanced biocontrol services in artificially selected strains of Orius laevigatus - José Enrique Mendoza; Virginia Balanza; Amador Rodríguez-Gómez; Dina Cifuentes; Pablo Bielza (Journal of Pest Science, 2022)
Augmentative biological control in protected crops relies mainly on omnivorous predators. Their performance as biological control agents (BCA) depends on several characteristics of the species, which in turn may differ among strains within a species. We have recently reported the achievement of two Orius laevigatus (Hemiptera: Anthocoridae) strains showing a significant larger body size or better fitness when feeding on pollen, two characteristics having a key impact on field performance. However, selection towards a specific trait might result in trade-offs, such as reduced predation capacity, which may impair control efficiency. Therefore, the predation capacity of these selected populations was tested in laboratory as a first step prior to its field use. Functional response to different densities of Frankliniella occidentalis (Thysanoptera: Thripidae) (adults and larvae) and Myzus persicae (Hemiptera: Aphididae) (nymphs) were studied in the large-sized and pollen-tolerant O. laevigatus strains in comparison with commercial and wild populations. A type-II functional response was observed regardless of the population. Body size was significantly related to thrips but not to aphid predation. The large-sized strain showed a superior predation capacity, both on thrips larvae and especially on adult thrips, although not on aphids. Therefore, the larger body size of the selected strain may increase its effectiveness as BCA of thrips. Regarding the pollen-tolerant strain, no trade-offs were observed in predation rates on adults or larvae of thrips, but it showed higher predation capacity on aphid nymphs, suggesting an expanded prey range. Implications of such enhanced biocontrol services on crop protection are also discussed.